Enhancing Students’ Performance in Professional Accounting Examination - Adibah Jamaluddin; Melissa Mam Yudi; Siti Syaqilah Hambali; Nazreen Sahol Hamid; Siti Aisyah Kamaruzaman (Communications of International Proceedings, 2020)
Possessing a professional accounting qualification means one is halfway through becoming a chartered accountant (CA) in Malaysia. However, due to the challenging nature of professional accounting examinations, candidates are struggling to complete the course timely, hence deterring the process of becoming a CA. Therefore, this paper focuses on three strategies - learning approach, study skills and learning pedagogy as a means for students to pass their professional accounting examination successfully.  Review of relevant literature revealed that by adopting a deep approach to learning, frequent self-testing using past examination questions and applicating a teacher-centred pedagogy as part of the learning process could elevate students’ performance. These findings may offer groundwork for empirical research to be conducted that may be beneficial to all students, tuition providers and the professional bodies.
Keywords: Professional qualifications; Academic performance; study skills.